The Socio-environmental or Socio-cultural Conflicts in Peru Understood from the Theory of Law - Peña Jumpa, Antonio (2014)
In this article, the author analyzes the complexity of a common problem in many parts of the world: social conflicts, putting emphasis on socio-environmental ones. Consequently, he starts addressing the social conflict concept and its elements, to approximate to its comprehension through various conceptions of the Theory of Law.Finally, the author provides a socio-anthropological analysis of Law in order to understand the importance of the knowledge of structural and systemic causes of socio-environmental conflicts and outlines an alternative solution.